2019
DOI: 10.1007/s10815-019-01436-7
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 2 regulates cumulus differentiation under the control of the oocyte

Abstract: Purpose We first assessed regulation of FGF2 expression in cumulus cells by FSH and oocyte-secreted factors during in vitro maturation (IVM). Then, we tested the hypothesis that FGF2 regulates meiotic progression, cumulus expansion, and apoptosis in cumulus-oocyte complexes (COC) undergoing IVM. Methods In vitro maturation of bovine COC was utilized as a model to assess regulation of FGF2 expression by FSH and oocytesecreted factors (via microsurgical removal of the oocyte), as well as effects of graded doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…These results agree with previous literature indicating that FGF2 added to regular IVM medium (carrying hormones) improves the degree of cumulus expansion and nuclear maturation [ 48 , 49 ]. Moreover, Barros et al [ 50 ] observed that FGF2 enhanced meiotic resumption, decreased cumulus cell dissociation, and inhibited the apoptosis on cumulus cells. However, Kobayashi et al [ 35 ] reported deficient cleavage rate after supplementation of the MM with FGF2 when the medium was lacking hormones.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with previous literature indicating that FGF2 added to regular IVM medium (carrying hormones) improves the degree of cumulus expansion and nuclear maturation [ 48 , 49 ]. Moreover, Barros et al [ 50 ] observed that FGF2 enhanced meiotic resumption, decreased cumulus cell dissociation, and inhibited the apoptosis on cumulus cells. However, Kobayashi et al [ 35 ] reported deficient cleavage rate after supplementation of the MM with FGF2 when the medium was lacking hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, FGF17 belongs to the FGF8 subfamily and likely activates the same receptor as FGF8 (Zhang et al, 2006). Moreover, follicle stimulating hormone and oocytes stimulate the expression of FGF2 in bovine cumulus cells, whereas supplementation with recombinant FGF2 promotes the meiotic resumption of oocytes and suppresses PTGS2 and TNFAIP6 expression during maturation cultures (Barros et al, 2019). This suggests that FGF2 exerts suppressive effects on cumulus expansion in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the expansion of TE in early development depends on FGF in mice, and that this expansion, which is dependent on FGF, occurs more in late stages in humans. The actions of FGF family members begin in the initial steps of reproduction mechanisms, therefore, FGF-10 expression has been detected in theca cells and ovarian stromal cells in humans [ 88 ], and FGF-2 and FGF-10 have been shown to increase the survival and proliferation of cumulus cells, increasing blastocyst development rates in bovine, sheep, and yak, in in vitro cultures [ 89 , 90 , 91 , 92 ]. Another family member, FGF-18, seems to regulate steroidogenesis in the fetal ovary [ 93 ].…”
Section: Growth Factors and Early Developmentmentioning
confidence: 99%